(untitled) (Jurnal Teknodik, 2015)
Abstrak: Fokus penelitian ini adalah penerapan parenting berbasis e-learning dalam mengembangkan kemampuan mendidik anak. Tujuan penelitian adalah untuk mengetahui: (1) penyelenggaraan program parenting di komunitas Institut Ibu Profesional (IIP) di Bandung, (2) pembelajaran parenting yang berbasis e-learning yang diselenggarakan oleh komunitas Institut Ibu Profesional, (3) perkembangan kemampuan mendidik anak pada anggota komunitas IIP Bandung setelah mengikuti program parenting dan pembelajaran parenting berbasis e-learning, dan (4) factor pendukung dan penghambat perkembangan kemampuan mendidik anak pada anggota. Metode penelitian menggunakan deskriptif dengan jumlah sampel sebanyak 20 orang. Kesimpulan hasil penelitian adalah sebagai berikut: (1) penyelenggaraan program parenting, diselenggarakan dengan pendekatan pendidikan orang dewasa melalui tahapan perencanaan, pelaksanaan, dan evaluasi, (2) pembelajaran dilaksanakan dalam kelas virtual syncronous (kelas online), (3) perkembangan kemampuan mendidik anak peserta setelah mengikuti pembelajaran e-learning, pada skala baik dan sangatbaik, dan (4) faktor penghambat dan pendukung perkembangan kemampuan mendidik anak dipengaruhi faktor internal yaitu diri orang tua dan eksternal yaitu pembelajaran parenting berbasis e-learning. Kata kunci: Manajemen Program, Parenting, e-learning, Kemampuan Mendidik Anak. Â Abstract: The focus of this research is the implementation of e-learning based parenting program in advancing the skill to educate children. The objectives of this research are to obtain information about: (1) the implementation of a parenting program in Professional Mother Institute (IIP) community members in Bandung, (2) the process of elearning- based parenting program in Professional Mother Institute (IIP) community members, (3) the development of the skill to educate children in the IIP community members in Bandung after attending the parenting programs and experiencing the process of e-learning-based parenting program, and (4) the factors supporting and inhibiting the development of the skill to educate children in IIP community members. The method usedwas descriptive research with a sample of 20 people. The conclusions of this research are: (1) the implementation of an e-learningbased parenting program was conducted with an adult education approach through the stages of planning, implementation, and evaluation, (2) the research was conducted in a synchronous virtual classroom (online classes), (3) the skill to educate children had developed after following the e-learning-based parenting program; on a scale of good and very good, and (4) the inhibiting factors and supporting factors of developing the skill to educate children are influenced by internal aspect, namely parents and external aspect namely the learning process of e-learningbased parenting program. Key words: Program Management, Parenting, e-learning, Child Education Skill.